The relationship between multisensory stimulus-integrated foreign language learning models and students’ psychological states and language skill development-an empirical analysis using the global learning assessment database - Zhan, Liu; Cheng, Jie (Frontiers in Psychology, 2025)
IntroductionThis study explores the impact of multisensory stimulus-integrated foreign language learning models on students’ psychological states and the development of language skills. The research focuses on how different combinations of sensory stimuli—visual, auditory, and tactile—affect learning anxiety, motivation, self-confidence, and performance in listening, speaking, reading, and writing.MethodsAn empirical analysis was conducted using data from the Global Learning Assessment Database. Quantitative methods, including regression analysis and Structural Equation Modeling (SEM), were employed to assess the effectiveness of multisensory learning models. The study examined the effects of specific sensory combinations and the integrated model on both psychological and linguistic outcomes, with additional analysis of gender-based differences.ResultsFindings indicate that the visual—tactile model is particularly effective in reducing learning anxiety (regression coefficient = –0.52, p < 0.01), while the visual—auditory model significantly enhances learning motivation (regression coefficient = 0.48, p < 0.01). The fully integrated model (visual + auditory + tactile) yields the most balanced and significant improvements across all four language skills: listening comprehension (+32%, p < 0.001), speaking fluency (+33%, p < 0.001), reading comprehension (+31%, p < 0.001), and writing richness (+34%, p < 0.001). Gender analysis reveals that the integrated model most significantly boosts female motivation (coefficient = 0.51, p < 0.01) and male self-confidence (coefficient = 0.44, p < 0.01).DiscussionMultisensory learning models are shown to effectively enhance both psychological well-being and language proficiency. The integrated approach offers the most comprehensive benefits, providing strong empirical support and practical implications for optimizing foreign language instruction through sensory-rich strategies.